Laboratory Investigation of Micronized Lomashell Powder Effects on Asphalt Binder and Mix Performance - Alireza Roshan; Abbas Ghasemi (Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
Lomashell, a mineral stone derived from oyster shells and skeletons, is widely available in Iran and across the globe. Typically used for livestock feed due to its high calcium content, its production generates a considerable amount of discarded fine grains. This research focused on incorporating micronized Lomashell as additive for asphalt pavement to enhance performance and environmental sustainability. The impact of this powder on the rheological and physical properties of two common asphalt binders was evaluated. Moisture resistance, rutting, and permanent deformation of Lomashell-enhanced asphalt mixtures were also examined. The results indicate significant improvements in rheological properties and dynamic shear rheometer parameters upon Lomashell addition. Moisture sensitivity was enhanced, as demonstrated by the indirect tensile strength test. Adding 7% of this material to the asphalt mixture enhanced indirect tensile strength by 12% compared to control. Furthermore, utilizing the Hamburg wheel-tracking device (HWTD), it was observed that inclusion of this powder enhanced resistance against permanent deformation, as evidenced by the rutting resistance index (RRD) values. Effective high-speed shear mixing is emphasized for binder modification, as revealed by scanning electron microscopy analysis. These findings highlight Lomashell’s positive influence on the overall performance and durability of the asphalt mixtures, reducing rutting and enhancing resistance against permanent deformation. Utilizing this powder as asphalt additive holds promise for improving functionality and addressing environmental concerns, contributing to sustainable infrastructure development.